CD44v3 and CD44v6 isoforms on T cells are able to discriminate different disease activity degrees and phenotypes in systemic lupus erythematosus patients. (April 2019) - Novelli, L; Barbati, C; Ceccarelli, F; Perricone, C; Spinelli, F R; Alessandri, C; Valesini, G; Perricone, R; Conti, F
Background: Adhesion molecule CD44 contributes to T cell migration into target organs. A higher expression of CD44v3 and v6 isoforms has been identified on T cells from systemic lupus erythematosus (SLE) patients. The aim of this study was to investigate the expression of CD44v3/v6 on T cells of SLE patients in order to evaluate their correlation with clinical features. Methods: Sixteen healthy subjects (HSs) and 33 SLE female patients were enrolled. Fifteen patients were in remission (Systemic Lupus Erythematosus Disease Activity Index-2000 (SLEDAI-2K) = 0) and 18 patients had an active disease (SLEDAI-2K ≥ 4). Experiments were conducted by flow cytometry. Results: Expression of CD44v3 on CD4 + and CD8 + T cells was higher in active patients compared to HSs ( p  = 0.0097 and p  = 0.0096). CD44v3 on CD8 + T cells was also higher in active patients compared to patients in remission ( p  = 0.038). CD44v6 was higher on CD4 + and CD8 + T cells from active patients compared to HSs ( p  = 0.003 and p  = 0.0036) and to patients in remission ( p  = 0.01 and p  = 0.02). In active patients the ratio CD44v3/v6 was unbalanced towards isoform v6 on both T cell populations. In a receiver operating characteristic curve analysis, CD44v6 on CD4 + T cells was the most sensitive and specific one (specificity of 81.8%, sensitivity of 75%). Expression of CD44v6 on CD4 + and CD8 + T cells correlated with the SLEDAI-2K ( p  = 0.03, r  = 0.38 and p  = 0.02, r  = 0.39). CD44v6 and CD44v3 on CD8 + T cells associated with nephritis and arthritis ( p  = 0.047 and p  = 0.023). Conclusions: CD44v3/v6 can be used as biomarkers of disease activity and phenotypes; isoform v6 on CD4 + T cells can be useful as a diagnostic biomarker.